Anthracycline‐based chemotherapy in metastatic endometrial carcinoma: An update. Issue 2 (26th November 2012) - Colloca, Giuseppe; Venturino, Antonella
Abstract The purpose of this review is to analyze clinical evidence about the activity and efficacy of anthracycline‐based chemotherapy in metastatic endometrial cancer and to identify the most important preclinical findings that would address future clinical trials. A literature search of published studies was undertaken. Studies were selected by predefined criteria. Clinical trials and preclinical studies were analyzed. The search identified eight phase 3 and 13 phase 2 clinical trials of patients with metastatic endometrial carcinoma treated with an anthracycline‐based regimen. The planned dose intensity of the anthracycline had no effect on response rates and survival. Survival increased for patients with a good performance status, and sometimes the duration of responses to anthracycline monotherapy can be very long‐lasting. The major findings of anthracycline resistance in preclinical models are reported. Possible future biomarkers targeting mechanisms of anthracycline resistance are suggested, and efforts to define a molecular classification of endometrial cancer are desirable.